Assessing lifestyle risk factors and inequalities in health outcomes in most deprived communities in Wales - Song, Jiao; Akbari, Ashley; Cox, Caryn; May, Leon; Watkins, Williams; Thomas, Sarah; Aitken, Sarah; King, William (International Journal of Population Data Science, 2018)
Introduction The Inverse Care Law (ICL) programme in Wales was piloted in Aneurin Bevan (AB) and Cwm Taf (CT) University Health Boards, chosen due to being located in areas of Wales which experience some of the most significant health inequalities and lower life expectancy and potential to effect change. Objectives and Approach The programme is aiming to address inequalities in health outcomes between the most and least deprived communities in Wales and implement targeted interventions towards lifestyle risk factors, such as poor diet, physical inactivity, smoking and high alcohol intake. The project collaborated with multiple stakeholders within the Health Boards, Swansea and Cardiff University and Public Health Wales to ensure the correct outcomes were identified and measured. The Welsh Longitudinal General Practice (WLGP) data held in Secure Anonymised Information Linkage (SAIL) databank was used to extract clinically relevant information for evaluation, with the Welsh Demographic Service Dataset (WDSD) providing demographic characteristics. Results Between AB and CT University Health Boards, from February 2015 to November 2016, over 7000 people who were offered a health check completed one at a participating General Practice. 96% of these were in the three most deprived Welsh Index of Multiple Deprivation (WIMD) quintiles. 51% were referred within primary care for follow up based on their health check results, 71% were overweight/obese, and 20% were identified as current smoker of within which 28% were referred to smoking sensation services. Alchohol usage and other health issues have also been investigated. For example, 20% of those tested for blood pressure had an elevated result and 24% were subsequently prescribed anti-hypertensive medication. Conclusion/Implications Results showed risks have been identified from health checks and targeted interventions were introduced based on the results. Repeated analysis in future should be used to further evaluate the effectiveness of the interventions longitudinally. Outcomes are reported back on a scheduled basis to monitor and improve the implementation across Wales.